BEBERAPA ASPEK APLIKASI ANTIDUMPING AGREEMENT PADA NEGARA SEDANG BERKEMBANG - FX. Joko Priyono (Masalah-Masalah Hukum, 2010)
Principle of fair competition is one of some principles in WTO agreements. Dumping is regarded as unfair pratice as stipulated in the Agreement on Anti Dumping and can be charged by countereiling duty. There are three elements to determine dumpng namely dumping price, injury and causal link. Dispute on dumping calls for much time and very tiring. Developing countries as defendadt has to provide human resources especially lawyer and economist to fight a suit of dumping from developed countries. According Article 15 ADA, regarding special and different treatment for Developing Countries, stipulates that they will be treated by "countructive remedies" but up till now there is no progres to formulate clearly